Characterization of Liver-Specific Functions of Human Fetal Hepatocytes in Culture. Issue 6 (June 2015) - Chinnici, Cinzia Maria; Timoneri, Francesca; Amico, Giandomenico; Pietrosi, Giada; Vizzini, Giovanni; Spada, Marco; Pagano, Duilio; Gridelli, Bruno; Conaldi, Pier Giulio
This study was designed to assess liver-specific functions of human fetal liver cells proposed as a potential source for hepatocyte transplantation. Fetal liver cells were isolated from livers of different gestational ages (16-22 weeks), and the functions of cell preparations were evaluated by establishing primary cultures. We observed that 20- to 22-week-gestation fetal liver cell cultures contained a predominance of cells with hepatocytic traits that did not divide in vitro but were functionally competent. Fetal hepatocytes performed liver-specific functions at levels comparable to those of their adult counterpart. Moreover, exposure to dexamethasone in combination with oncostatin M promptly induced further maturation of the cells through the acquisition of additional functions (i.e., ability to store glycogen and uptake of indocyanine green). In some cases, particularly in cultures obtained from fetuses of earlier gestational ages (16-18 weeks gestation), cells with mature hepatocytic traits proved to be sporadic, and the primary cultures were mainly populated by clusters of proliferating cells. Consequently, the values of liver-specific functions detected in these cultures were low. We observed that a low cell density culture system rapidly prompted loss of the mature hepatocytic phenotype with downregulations of all the liver-specific functions. We found that human fetal liver cells can be cryopreserved without significant loss of viability and function and evaluated up to 1 year in storage in liquid nitrogen. They might, therefore, be suitable for cell banking and allow for the transplantation of large numbers of cells, thus improving clinical outcomes. Overall, our results indicate that fetal hepatocytes could be used as a cell source for hepatocyte transplantation. Fetal liver cells have been used so far to treat end-stage liver disease. Additional studies are needed to include these cells in cell-based therapies aimed to treat liver failure and inborn errors of metabolism.